2017
DOI: 10.14687/jhs.v14i1.4383
|View full text |Cite
|
Sign up to set email alerts
|

The effects of socio-demographic factors and work-life balance on employees’ emotional exhaustion

Abstract: The object of the research is observing the effects of socio-demographic factors and work-life balance on employees' emotional exhaustion. The sample of the research consists of 261 participants in retailing, education, service, industry and logistics sectors. In line with the theoretical background, proper methods that are hierarchical regression analysis and analysis of variance (ANOVA) are implemented. The contribution of the research to the existing literature is exploring the relationship between socio-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Various studies identified that conflicts between work and private life are positively related to burnout in various occupational groups and industries (e.g., Allen et al, 2000 ; Brauchli et al, 2011 ; Vassos and Nankervis, 2012 ; Demerouti et al, 2018 ; Fenwick et al, 2018 ; Wu et al, 2018 ). Similarly, emotional exhaustion decreases with increasing work-life accordance (Tugsal, 2017 ). The time-related role conflicts between work and private life do not only relate to the family, but also to conflicts outside the family such as leisure time and engagement (friends, volunteer work, etc.).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies identified that conflicts between work and private life are positively related to burnout in various occupational groups and industries (e.g., Allen et al, 2000 ; Brauchli et al, 2011 ; Vassos and Nankervis, 2012 ; Demerouti et al, 2018 ; Fenwick et al, 2018 ; Wu et al, 2018 ). Similarly, emotional exhaustion decreases with increasing work-life accordance (Tugsal, 2017 ). The time-related role conflicts between work and private life do not only relate to the family, but also to conflicts outside the family such as leisure time and engagement (friends, volunteer work, etc.).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, emotional exhaustion decreases with increasing worklife accordance (Tugsal, 2017). The time-related role conflicts between work and private life do not only relate to the family, but also to conflicts outside the family such as leisure time and engagement (friends, volunteer work, etc.…”
Section: Avoidance Of Role Conflicts Due To Working Hoursmentioning
confidence: 98%